Variability of respiratory rate measurements in children suspected with non‐severe pneumonia in north‐east Tanzania. Issue 2 (12th December 2016) - Muro, Florida; Mosha, Neema; Hildenwall, Helena; Mtei, Frank; Harrison, Nicole; Schellenberg, David; Olomi, Raimos; Reyburn, Hugh; Todd, Jim
Abstract: Objective: Measurement of respiratory rate is an important clinical sign in the diagnosis of pneumonia but suffers from interobserver variation. Here, we assess the use of video recordings as a quality assurance tool that could be useful both in research and in training of staff. Methods: Respiratory rates (RR) were recorded in children aged 2–59 months presenting with cough or difficulty breathing at two busy outpatient clinics in Tanzania. Measurements were repeated at 10‐min intervals in a quiet environment with simultaneous video recordings that were independently reviewed by two paediatricians. Results: Eight hundred and fifty‐nine videos were sent to two paediatricians; 148 (17.2%) were considered unreadable by one or both. For the 711 (82.8%) videos that were readable by both paediatricians, there was perfect agreement for the presence of raised RR with a kappa value ( κ ) of 0.85 ( P < 0.001); and in 476 (66.9%) cases, both paediatricians agreed on the RR within 2 breaths per minute (±2 bpm). A reported illness of 5 days or more was associated with unreadable video recordings (OR = 3.44, CI: 1.5–6.08; P < 0.001). The multilevel model showed that differences between observers accounted for only 13% of the variability in RR. Conclusion: Video recordings are reliable tools for quality assurance of RR measurements in children with suspected pneumonia. Videos with a clear view of respiratory movements may also be useful in training primary healthcare staff.